STUDENTS’ READING AND LISTENING COMPREHENSION BASED ON THEIR LEARNING STYLES - Magfirah, Titing (International Journal of Education, 2018)
This research aims to know whether there is a significant difference between reading and listening comprehension scores based on learning styles: visual and auditory, of the eighth grade students of SMPN 4 Pallangga Gowa in academic year 2016-2017. This study used quantitative method and causal-comparative design. The instruments of this study included learning style questionnaire, reading comprehension test, and listening comprehension test. Further, it used independent sample t-test to analyze the data from learning styles questionnaire, and reading and listening comprehension scores. Findings of the result reveal that there was no significant difference between students’ reading and listening comprehension scores based on two groups’ learning styles: visual and auditory. The result shows that sig. values of reading comprehension based on two learning styles, visual and auditory, were 0.592 and 0.594, respectively, which were greater than p-value (0.05). Similarly, the sig. values of two learning style groups in listening comprehension performance were the same, namely 0.954. It means that both sig. values were greater than p-value (0.954 0.05). Hence, it can be concluded that H0 was accepted and Ha was rejected. Clearly, from the result, it can be said that learning style is not the only one factor affecting students’ reading and listening comprehension scores.